PROBLEMATIKA PENGELOLAAN TANAH WAKAF PRODUKTIF BERBASIS MASJID: (Studi Kasus Terhadap Tanah Wakaf Masjid Di Kota Palembang) - Rochmiyatun, Siti (Nurani, 2018)
Waqf is one of the most highly recommended worship in the teachings of Islam, to be used by someone as a means of distributing gift by Allah SWT to him. The practice of waqf is of great value to socio-economic, cultural life. Management of Waqf land productively mosques in Palembang City has been implemented, but in general most mosques still do not manage Waqf land mosque productively. The problematic for managing the Waqf land of a mosque productively are, 1. The legal substance (AIW substance of Waqf land) may impede implementation; 2. Understanding of some Nazhir/ Mosque management on the management of productive Waqf land is still low; 3. The general understanding of the community about the management of productive Waqf land is still low; 4. The ability of Nazhir/ Managers to manage and develop productive enterprises is still low; 5. Community culture does not encourage the implementation of productive waqf land management; 6. Community law culture is a legal awareness to implement the law, especially regarding the management and development of Waqf land productively low. Efforts that can be done to overcome the problematic is the Office of the Ministry of Religious Affairs and BWI, BWI Representative of South Sumatra should increase the socialization and comprehensive training of productive waqf management to mosque nazhir and the community around the mosque.